Dialogues and Dynamics - Interculturality in Theology and Religious Studies - Heinrich, Fritz; Schlarb, Cornelia; Schlarb, Egbert; Schröder, Ulrike (Universitätsverlag Göttingen, 2021)
This volume contains the texts from the symposium on the occasion of the 10th Anniversary of the M.A. Programme Intercultural Theology. The contributions address the challenges and consequences of an intercultural approach in academics as well as in the churches and in society. Since globalisation has significantly changed the face of contemporary Christianity in the 21st century, the task of doing theology has become more complex. The cultural, geographic and denominational varieties of Christianity worldwide challenge the traditional Western face of academic Christian theology and demand new and global forms of theological thinking across lines. Intercultural Theology seeks to embrace these dynamics with a constructive dialogue, opening up new spaces of collaborative thinking and academic reflection.